Perbandingan EVA, MVA dan FVA Perusahaan Sub Sektor Farmasi yang Terdaftar di BEI Pada Saat dan Sesudah Pandemi Covid 19 - Handayani, Tutut; Yulia, Iis Anisa; Fitrianti, Dewi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research investigates the financial performance of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during and after the COVID-19 pandemic by analyzing Economic Value Added (EVA), Market Value Added (MVA), and Financial Value Added (FVA). The study aims to determine the impact of the pandemic on these companies' ability to create value for their shareholders and improve financial performance. A sample of 11 pharmaceutical companies was selected using purposive sampling, focusing on firms that have consistently reported financial data before, during, and after the pandemic. The Wilcoxon Signed Ranks Test was employed to assess the significance of differences in performance metrics over the two periods. Results show that there is no significant difference in the financial performance during and after the pandemic when measured using the EVA and FVA methods, indicating resilience in the intrinsic value creation capabilities of these companies. However, a notable difference was found in the MVA, reflecting changes in market perceptions and investor confidence. These findings suggest that while intrinsic financial metrics remained stable, external market factors significantly influenced company valuations.